Summer distribution and community structure of surface water mesozooplankton from the eastern Mediterranean Sea - Isinibilir Melek; Aker Vedat; Türkeri Ezgi E. (Oceanological and Hydrobiological Studies)
The zooplankton community structure and its relationship with environmental parameters were evaluated in the surface waters (0–50 m) of the eastern Mediterranean (the Aegean Sea's coastal waters and the Levanine Sea's coastal and offshore waters), from coastal waters to open sea waters, during the summer for two years. A total of 157 species/groups were registered in the study area. Copepods, cladocerans, doliolids, meroplankton and appendicularians represented the most important zooplankton groups. Five copepod species (Corycaeus [Onychocorycaeus] ovalis, Goniopsyllus clausi, Oncaea scottodicarloi, Sapphirina bicuspidata and Scaphocalanus curtus) have been recorded for the first time in Turkish coastal regions; three species (Centropages bradyi, Goniopsyllus clausi and Oncaea scottodicarloi) had not previously been found in the Aegean Sea; and one species (Goniopsyllus clausi) has been added for the first time to the eastern Mediterranean fauna. Moreover, Pleopis schmackeri was already found to be present in both the Aegean Sea and Mediterranean coasts of Turkey in August 2006. Dominant species varied from the coastal waters to open waters. A small number of species belonging to the coastal community (e.g. Penilia avirostris, Pseudevadne tergestina, Oithona plumifera, Paracalanus parvus and Centropages kroyeri) dominated all coastal areas. In contrast, the open water stations were characterised by the presence of typically epipelagic species of the Mediterranean Sea (e.g. Calocalanus spp., Clausocalanus furcatus, Lucicutia flavicornis, Mecynocera clausi, Farranula rostrata, Oncaea scottodicarloi and Oncaea mediterranea).